Secular and orbital-scale variability of equatorial Indian Ocean summer monsoon winds during the late Miocene - C. T. Bolton; E. Gray; E. Gray; W. Kuhnt; A. E. Holbourn; J. Lübbers; K. Grant; K. Tachikawa; G. Marino; G. Marino; E. J. Rohling; E. J. Rohling; et al. (Climate of the Past, 2022)
In the modern northern Indian Ocean, biological productivity is intimately linked to near-surface oceanographic dynamics forced by the South Asian, or Indian, monsoon. In the late Pleistocene, this strong seasonal signal is transferred to the sedimentary record in the form of strong variance in the precession band (19–23 kyr), because precession dominates low-latitude insolation variations and drives seasonal contrast in oceanographic conditions. In addition, internal climate system feedbacks (e.g. ice-sheet albedo, carbon cycle, topography) play a key role in monsoon variability. Little is known about orbital-scale monsoon variability in the pre-Pleistocene, when atmospheric CO2 levels and global temperatures were higher. In addition, many questions remain open regarding the timing of the initiation and intensification of the South Asian monsoon during the Miocene, an interval of significant global climate change that culminated in bipolar glaciation. Here, we present new high-resolution (<1 kyr) records of export productivity and sediment accumulation from International Ocean Discovery Program Site U1443 in the southernmost part of the Bay of Bengal spanning the late Miocene (9 to 5 million years ago). Underpinned by a new orbitally tuned benthic isotope stratigraphy, we use X-ray fluorescence-derived biogenic barium variations to discern productivity trends and rhythms. Results show strong eccentricity-modulated precession-band productivity variations throughout the late Miocene, interpreted to reflect insolation forcing of summer monsoon wind strength in the equatorial Indian Ocean. On long timescales, our data support the interpretation that South Asian monsoon winds were already established by 9 Ma in the equatorial sector of the Indian Ocean, with no apparent intensification over the latest Miocene.